Enablers of the Use of Virtual Assistants by Students at a Nigerian University - Funmilola Olubunmi Omotayo; Faith Eloho Tosan (IJIE (Indonesian Journal of Informatics Education), 2025)
Virtual assistants are emerging technologies that are gaining prominence with the advancement in Artificial Intelligence and Human-Computer Interaction. The widespread acceptance and use of technology depend on the willingness of users to use the technology and on several other factors. This study was designed to investigate the enablers of the use of virtual assistants (VAs) by students at a Nigerian University. The study was anchored on three theories - Uses and Gratifications Theory, the Media Richness Theory and the Extended Unified Theory of Acceptance and Use of Technology (UTAUT2). A structured questionnaire was used to collect data from 368 students who used VAs. Findings showed that the enablers (utilitarian benefits, hedonic motivation, multiple cues, personal focus, use of natural language and hedonic motivation) have a strong positive correlation (r = 0.754, 0.681, 0.614, 0.667, 0.581 and 0.686 respectively) and significant relationship (p=0.00< 0.05) with the use of VAs. There was a joint influence of the enablers on the use of VAs (F = 209.861, R2 = 0.773, p= 0.000< 0.005), showing that these enablers accounted for 77.3% of the variance in the use of VAs. The findings provide a better understanding of the determinants of VA adoption and use for educational purposes and which enablers need to be promoted to increase adoption and use.